THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE OF MENSTRUAL HEALTH MANAGEMENT AMONG ADOLESCENT GIRLS IN RURAL AREA - Yulianti Wulandari; Rachmawaty M. Noer; Alifia Nur Anniza; Fitri Juliana (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
ABSTRACT Menstrual health management is a way to maintain cleanliness and health when women are menstruating, poor knowledge and attitudes can lead to poor Menstrual Health Management which can cause diseases of the female reproductive organs. Objective: This study is to determine the relationship between knowledge and attitudes of adolescent girls with menstrual health management at the adolescent health post in the working area of Baran Timur village. Methods: This study is a quantitative study with a cross-sectional approach. the population in this study were adolescent girls who had menstruated with a total of 87 respondents who were taken through total sampling. Data collection using questionnaires and data analysis using chi- square test. Results: Bivariate analysis showed a p value of 0.016 for the relationship between knowledge and menstrual health management and a p value of 0.029 for the relationship between attitude and menstrual health management where the value is less than 0.05 so that Ha is accepted which means there is a relationship between knowledge and attitude of adolescent girls with menstrual health management. Conclusion: It is expected to further improve the knowledge of menstrual health management so that attitudes become better. Keywords: Menstrual health management, knowledge, attitude, adolescent girls